The Improvement on the Boundedness and Norm of a Class of Integral Operators on Lp Space - Lifang Zhou; Jin Lu (Journal of Function Spaces)
We prove the condition “c is neither 0 nor a negative integer” can be dropped on the boundedness of a class of integral operators Sa,b,c on Lp space, which improves the result by Krues and Zhu. Besides, the exact norm of Sa,b,c on Lp space is also obtained under the assumption c=n+1+a+b.